Uji Daya Hambat Ekstrak Etanol 96% Daun Jeruk Purut (Citrus Hystrix D.C. ) Terhadap Propionibacterium Acnes - Fitriyanti Fitriyanti; Syaid Nofal Assegaf; Karunita Ika Astuti (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Acne is a disease on the surface of the skin that often causes pain and leaves red, pus-filled spots. The plant that can be developed as an antibacterial is the citrus tribe which is also useful as a flavor enhancer in cooking, namely kaffir lime leaves (Citrus hystrix D.C). The purpose of this study was to test the activity of 96% ethanol extract of kaffir lime leaves against the inhibition of the acne-causing bacteria Propionibacterium acnes. In testing the antibacterial activity of this study using a good method. Based on the results of phytochemical screening, the extract was positive for flavonoids, saponins, tannins, and steroids. Based on the test results of measuring the diameter of the inhibition zone of kaffir lime leaf extract at a concentration of 100%; 80%; 60%; 40%; 20%; and 10% by 22.133 mm; 19,333 mm; 17,266 mm; 15,933 mm, 14.9 mm; and 12.133 mm. Data were analyzed using SPSS with Mann Whitney to obtain a significant value for each concentration variation, with a value of sig <0.05, which means that there are significant differences in each treatment group.